2020
DOI: 10.21037/mhealth-2019-di-13
|View full text |Cite
|
Sign up to set email alerts
|

Chat-based hotlines for health promotion: a systematic review

Abstract: Background: Chat-based hotlines use online messaging services or popular chat applications such as WhatsApp, Facebook Messenger, and WeChat, to connect users to trained health providers or staff. Chatbased hotlines can provide real-time communication between health providers and patients. Methods:The evidence for chat-based hotlines for health promotion has not been reviewed systematically.Electronic databases (PubMed, Cochrane Database, Google Scholar) were searched to identify Englishlanguage studies describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…However, those users interacting only by chat reported consistently worse experiences relative to users who called the helpline. While offering chat may expand access to services, users contacting the helpline by chat may experience delayed response times relative to users contacting the helpline by phone, which could be a factor in explaining the relatively worse experiences reported by those users (Brody et al, 2020 ; Predmore et al, 2017 ). As helplines increasingly add online chat options, determining best practices for providing high quality interactions and needed care may be an important implementation consideration.…”
Section: Discussionmentioning
confidence: 99%
“…However, those users interacting only by chat reported consistently worse experiences relative to users who called the helpline. While offering chat may expand access to services, users contacting the helpline by chat may experience delayed response times relative to users contacting the helpline by phone, which could be a factor in explaining the relatively worse experiences reported by those users (Brody et al, 2020 ; Predmore et al, 2017 ). As helplines increasingly add online chat options, determining best practices for providing high quality interactions and needed care may be an important implementation consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Messaging applications such as WhatsApp, Facebook Messenger, WeChat, and Line also have myriad applications in healthcare. Chat-based hotlines can connect users with healthcare professionals in real time and could have potential in crisis settings where other communications may be limited in a rapidly changing situation [ 58 ]. Since photos and video can be transmitted through instant messaging, dermatology teleconsultations through messaging applications have been piloted and are well-received by patients [ 59 ].…”
Section: Other Social Media Applications and Dermatologymentioning
confidence: 99%
“…Hotlines have previously been shown to help manage health issues, such as anxiety depression, and suicide prevention. 9 , 10 Previous research has found that telephone helplines are beneficial to people dealing with suicidal ideations 11 because users feel safer to ask questions on sensitive issues such as depression, death, and finance compared to a web-based approach. 12 …”
Section: Introductionmentioning
confidence: 99%